KCDC — The KASCADE Cosmic-ray Data Centre. (July 2015) - Haungs, A; Blumer, J; Fuchs, B; Kang, D; Schoo, S; Wochele, D; Wochele, J; Apel, W D; Arteaga-Velázquez, J C; Bekk, K; Bertaina, M; Bozdog, H; et al.
Abstract: KCDC, the 'KASCADE Cosmic-ray Data Centre', is a web portal, where data of astroparticle physics experiments will be made available for the interested public. The KASCADE experiment, financed by public money, was a large-area detector for the measurement of high-energy cosmic rays via the detection of air showers. KASCADE and its extension KASCADE-Grande stopped finally the active data acquisition of all its components including the radio EAS experiment LOPES end of 2012 after more than 20 years of data taking. In a first release, with KCDC we provide to the public the measured and reconstructed parameters of more than 160 million air showers. In addition, KCDC provides the conceptional design, how the data can be treated and processed so that they are also usable outside the community of experts in the research field. Detailed educational examples make a use also possible for high-school students and early stage researchers.